FILSAFAT MANUSIA ALI SHARI'ATI - Wazin Baihaqi (Al Qalam, 2009)
The philosophy of man, according to Ali Shariati, covers several ideas. He explains the philosophy of man by stating that the verses of the Qur'an much more use the symbolic language. The symbols stated in the Qur'an are then interpreted by Ali Shariati to express his concept on the philosophy of man.The history of the creation of Adam telling that Adam is able to mention the names of several objects around him is a symbol of the intellectual ability of man. Performing the angels bow because of Adam's intellectual capability shows us the appreciation of Islam to humanism. The statement of the Qur'an that human spirit is created from a part of God's spirit is interpreted that human is endowed power (at a certain levels) by God in which it is, as a matter of fact, a manifestation of the attributes of Allah. Due to his intellectual capability and his power, man is, then, appointed to be His khalifah in the World.Ali Shariati states that human is two-dimensional beings. This conclusion constitutes an interpretation of several verses of the Qur'an stating that man is made of loam ( as a symbol of lowness) and a part of God's spirit (as a symbol of holiness). In order not to be fell into one of the extreme poles, man needs religion, God, holy book and prophet that have two-dimensional aspects, the mundane and the beyond. The only religion that has both of these aspects is Islam.